Det intelligente kød: Træk af en begrebshistorie fra Descartes til Merleau-Ponty - Sejten, Anne Elisabeth (Academic Quarter | Akademisk kvarter, 2010)
Anne Elisabeth Sejtens Det intelligente kød – træk af en begrebshistorie fra Descartes til Merleau-Ponty.(Intelligent flesh Features of a history of concepts from Descartes to Merleau-Ponty). The aim of the article is to reconstruct a piece of primarily French history of concepts, which from René Descartes to Maurice Merleau-Ponty shows that the position of flesh in the theory of cognition has grown quite prominent. In contrast to existing research, which by far is specifically philosophical with focus on connections between Husserl and Merleau-Ponty the article seeks to include a notable inheritance from the history of ideas from French philosophers of the Enlightenment Era, not least Diderot, where the flesh is the object of an actual philosophical consideration.